Tissue-adapted Tregs harness inflammatory signals to promote intestinal repair from therapy-related injury - Fischer, Julius C.; Göttert, Sascha; Giller, Maximilian; Heinrich, Paul; Fan, Kaiji; Khalid, Omer; Walther, Caroline N.; Drießlein, Maria; Nefzger, Sophie M.; Eisenkolb, Gabriel; Timnik, Vincent R.; Jarosch, Sebastian; et al. (Signal Transduction and Targeted Therapy, 2025)
Intestinal stem cells (ISCs) promote tissue repair after genotoxic or immune-mediated injury. However, ISCs are particularly sensitive to various stressors and primary targets of overwhelming immune responses, such as interferon γ (IFNγ)-mediated killing. In mouse models of radiation therapy-induced gut damage and in biopsies from patients who underwent allogeneic hematopoietic stem cell transplantation, we observed IFNγ expression by intestinal Treg cells. Treg cells leverage combined IFNγ and interleukin 10 (IL-10) stimulation of ISCs to nurture the growth of intestinal organoids through the activation of the mTORC1 and Myc pathways. Similarly, Treg cells or the combined addition of recombinant IFNγ and IL-10 promoted the regeneration of organoids after irradiation, and both cytokines were essential for ensuring epithelial regeneration following acute intestinal tissue injury in vivo. The exposure of organoids to growth factor-free culture conditions revealed distinct EGF-like properties of IFNγ and Wnt-like properties of IL-10. While IFNγ rapidly induced epithelial proliferation, it depleted the pool of ISCs in vitro. Only the combination of IFNγ and IL-10 led to epithelial proliferation and organoid growth while simultaneously ensuring ISC maintenance over time. Our results reveal a context-dependent role of inflammatory signaling in ISCs, through which Treg cells promote epithelial repair following therapy-induced injury.
CRIS-Team Scopus Importer:2025-12-05